(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Overactive Bladder (OAB) is a debilitating medical condition having the symptoms of urinary frequency and urgency with or without urge incontinence. Tolterodine was the first drug developed specifically for the treatment of OAB. It is a competitive muscarinic antagonist that exhibits similar affinities for muscarinic receptor subtypes M1 to M3. Tolterodine may be a more target specific drug that possesses stronger selectivity for the urinary bladder than for the salivary glands. In a pilot study in healthy volunteers, tolterodine was well-tolerated and showed greater function than on salivation. Objectives: To study the efficacy of tolterodine (ER) in relieving symptoms of overactive bladder with its adverse effects to determine the safety of the drug. Methods: This study was conducted at the Department of Urology, Chittagong Medical College Hospital, Chittagong, Bangladesh, from March, 2014 to June, 2015. Purposive sampling was done. Bladder diary was used for evaluating the symptoms of the patient during baseline and 08 weeks follow up. Perceived level of benefit of the patients was assessed and graded using Likert scale. Data analysis was conducted by SPSS version-21. Results: Out of 80 patients, 19 (23.75%) were male and 62 (76.25%) were female with a male: female ratio 1:3.2. The study revealed that the most of the patients, 48 (60.0%) were subjected to much benefit followed by 23 (28.75%) patients experienced little benefit and 09 (11.25%) patients with no benefit from the treatment. Conclusion: With mild form of side effects tolterodine showed a significant level of efficacy on overactive bladder. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 34-37